SISTEM KENDALI PEMICUK LEDAK DENGAN DETONATOR LISTRIK MENGGUNAKAN TELEPON GENGGAM BERDASARKAN SMS (SHORT MESSAGE SERVICE) - -, Subandi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
The use of explosives/bomb was always considered bad and frighten for society because of the recent terrorist act. In fact, not only in the military field, Bomb can be used for construction (reconstruction), mining exploration, dramatization movie scene or something else, but can not be denied its high risk. Be clear about the bomb technology is not widely explored whether the explosives themselves, trigger/detonator, especially control systems.Control using a Mobile based on SMS has been used widely, considering the advantages of this control that it is low cost, wide coverage, and do not need to design the transmitter and receiver. The message sent is the format of PDU (Protocol Data Unit), but is converted to text for easy monitoring, a microcontroller with at-command (command function for HP) will read and recognize those formats to start the next action according to the instructions sent via message. By Sending an SMS (boom) to the mobile server, then messages are forwarded to the microcontroller. The results show that the system works well if the character that is sent in complaince then the microcontroller will execute the program to activate the electric detonators, the ecplosive will be ignited and successfully detonated.